Rancang Bangun Aplikasi Penjualan Pakaian Pada Toko Denim Goods Surabaya - farid, muchammad; Sulistiowati, Sulistiowati; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Denim Goods is a stores that have average sales of approximately 150 transactions per mounth with the average income per month amounted to sixty million rupiah. With a large number of transactions at stores, stores manager have difficulty in doing data processing which includes the recording of incoming goods, sales transactions, best goods selling transactions, purchase reports, sales reports and reports of clothes stock. During this time the store is still applying the manual system and still use the notes in the recording of sales. Based on these problems then created an application that consist of sales transaction, the purchase transaction and the reports. The existence of this application is expected to provide ease in the sales process in running its business. In addition, the manager of the stores will get the best-selling goods reports, sales reports, reports of the purchase, and reports of clothes stock.